The importance of justifications and their impact on building the grammatical rule - Keadan, Siham Youisf (Journal of Arabic Language Sciences and Literature, 2023)
This study dealt with the importance of justifications and their impact on building the grammatical base in the light of what was approved by the Arabic grammar scholars and against the background of the efforts they made in this field. This topic, and the research relied on the inductive and analytical approach, by extrapolating and collecting everything related to the research topic from grammar books, understanding the scientific material and identifying the strengths that can be spoken about; In order for it to be an accurate subject that does not tend to boring overstatement or disturbing brevity, the scientific material is analyzed and each content is placed under its element according to the research plan. What follows is to make its meaning clear, and that the rationale is concerned with highlighting the relationships between words, as the grammatical relationships between words are obtained through their regularity in a specific order in the Arabic sentence, some of which are taken by reservation.
Keywords: Justifications; grammatical rule; Grammatical rank; justification effect